2017
DOI: 10.3126/nepjoph.v8i2.16992
|View full text |Cite
|
Sign up to set email alerts
|

Study of microbial growth on silicone tubes after transcanalicular laser-assisted dacryocystorhinostomy and correlation with patency

Abstract: Introduction:Intubation in primary transcanalicular laser assisted dacryocystorhinostomy (TCLADCR) is performed to increase the success rates. However, the associated inflammation and infection can have adverse effects. Objective: To study the microbial infection and drug susceptibility of extubated silicone tubes and final anatomical patency in patients undergoing TCLADCR. Materials and methods: A non-randomised prospective interventional study was conducted in a tertiary care eye centre. The study included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Chronic dacryocystitis is more common in females due to anatomically narrower lacrimal drainage system than in males leading to females coming for DCR more often. In this study as well there were a considerably greater number of female participants (29/6) with p-value of 0.288, which is consistent with previous studies [9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…Chronic dacryocystitis is more common in females due to anatomically narrower lacrimal drainage system than in males leading to females coming for DCR more often. In this study as well there were a considerably greater number of female participants (29/6) with p-value of 0.288, which is consistent with previous studies [9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…among our isolates may be linked to the low socioeconomic profile of the patients and poor hygiene habits. Similarly to our results, Nemati et al 18 and Goel et al 19 reported high rates of enteric floral growth among the gram-negative isolates obtained from silicone tubes.…”
Section: Discussionsupporting
confidence: 91%
“…The organisms isolated were not associated with the success rate of DCR in the studies by Ali et al 12 and Goel et al 19 However, Kim et al 13 reported that surgical failure and revision surgeries were associated with Pseudomonas infection. In our study, H. influenzae growth was associated with surgical failure, although we were unable to determine the exact relationship between the surgical failure and H. influenzae growth.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations